Knowledge, attitude, and practice towards anemia prevention among female students in Indonesia: a mixed method study - Lafi Munira; Pramon Viwattanakulvanid (International Journal of Evaluation and Research in Education (IJERE), 2024)
Based on the Indonesian national health survey in 2018, the prevalence of anemia in young women aged 15-34 was 48.9%. This study aimed to examine the influence of knowledge and attitude on anemia prevention practice and to identify reasons for not practicing anemia prevention among female high school students in Banjarmasin municipality, Indonesia. A mixed method sequential explanatory was applied for this study. The respondents are 350 female high school students from three senior high schools, chosen purposively for a cross-sectional study and followed by focus group discussion with 15 students and in-depth interviews with three teachers and four health workers. The results revealed that 254 (72.6%) female students had poor practice, 147 (42.0%) had poor attitude, and 169 (48.3 %) had poor knowledge related to iron deficiency anemia (IDA) prevention. Female students in the older age group (17-18 years old) (adjusted odds ratio/AOR 1.88, 95% CI 1.12, 3.16), studying at vocational school (AOR 1.85, 95% CI 1.05, 3.27), good knowledge (AOR 2.52, 95% CI 1.49, 4.26) were significant predictors on iron deficiency anemia (IDA) prevention. The qualitative findings found that the reasons for not practicing anemia prevention include poor knowledge about anemia practice prevention, dislike of iron tablets, and ineffective anemia education program due to poor coordination and communication between health workers and teachers. Effective anemia education programs at schools are needed to enhance students' knowledge related to anemia prevention.